The Effectiveness Of Warm Water Therapy And Deep Breathing Relaxation In Blood Pressure - Ni Made Ferayanti; Rizky Erwanto; Adi Sucipto (Fakultas Ilmu Keperawatan Universitas Islam Sultan Agung, Semarang, 2017)
Introduction: Prevalence of hypertension in Indonesia is 26.5% WHILEhile in Yogyakarta cases of hypertension as a cardiovascular disease that causes the highest deaths reached more than 80%, and the incidence rate is always increasing every year. From the results of interviews of 56 respondents and blood pressure measurement obtained 21 respondents who experienced hypertension. To overcome hypertension in elderly researchers combined two warm water foot soak therapy and deep breathing relaxation. The purpose of this research is to know the effectiveness of warm water foot soak therapy and deep breathing relaxation to blood pressure in elderly at Rumah Seni Seni Budi Dharma Yogyakarta. Methodology: This research is a quantitative research type, the method used quasi Experimental Desaign with pre and post test design control. Sampling using total sampling. Technique of collecting data by observation using digital sphygmomanometer. Data analysis using Paired simple t-test with significant value p <0,05. Result: The result of data analysis obtained by the respondent's blood pressure after the treatment therapies decreased significantly with pistol systolic and diastolic p value of 0.000. With an average systolic blood pressure difference before and after intervention of 22.71 mmHg and diastolic 11.94 mmHg. Discussion: There is a significant effect on decreasing systolic and diastolic blood pressure before and after treatment of warm foot bath and deep breath relaxation in hypertensive elderly at UPT Budi Dharma Yogyakarta Senior High School